Geoecological cartography and landscape mapping in Erechim (RS): contributions to territorial management - Oliveira-Costa, Jorge Luis; Orelus, Stephen Orlly (Aprender, 2025)
The spatial object of this research, the municipality of Erechim, located in the centre-north zone of the state of Rio Grande do Sul, is characterized by local landscape diversification, of the physical-natural elements and land uses, which are structurally determined mainly by the local geoecological conditions. This study aims to develop a geoecological analysis of the area of Erechim, considering, for this purpose, the dynamics of the landscapes and vulnerability. The study had as methodological procedures an state of art’ research, field research and mapping work. Based on cartographic/bibliographic review and data from field works, a map of the environmental units of the municipality of Erechim was elaborate at a scale of 1:50,000. This map, combined with the altimetric context of the study area, highlights the three main Environmental Units (EUs) of Erechim: (1) EU1 – Headwaters Sectors; (2) EU2 – Intermediate Sectors; (3) EU3 – Terminal Sectors. Based on the range values ​​of the UAs of Erechim and the environmental conditions, this analysis has pointed to a non-random pattern in the distribution of these UAs, which it appears to have a distribution structurally determined by specific local geoecological processes. The main highlight of this work it’s the significant fragility of the area, given the attributes of its zone of influence, with warning about the high rate of transformation of local ecosystems.